2011
DOI: 10.1007/s00442-011-2159-x
|View full text |Cite
|
Sign up to set email alerts
|

Seed bank survival of an invasive species, but not of two native species, declines with invasion

Abstract: Soil-borne seed pathogens may play an important role in either hindering or facilitating the spread of invasive exotic plants. We examined whether the invasive shrub Lonicera maackii (Caprifoliaceae) affected fungi-mediated mortality of conspecific and native shrub seeds in a deciduous forest in eastern Missouri. Using a combination of L. maackii removal and fungicide treatments, we found no effect of L. maackii invasion on seed viability of the native Symphoricarpos orbiculatus (Caprifoliaceae) or Cornus drum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 60 publications
2
13
1
Order By: Relevance
“…This study was conducted at Busch Wildlife Conservation Area (38.708 N, 90.718 W), a 6987-ha reserve in Saint Charles County, Missouri, USA. The area has approximately 1215 ha of oak-hickory forests with shrub layers often dominated by L. maackii , Orrock et al 2012. Density of L. maackii in invaded areas within the study area was 0.34-0.93 individuals/m 2 (Watling et al 2011), densities consistent with other studies (e.g., 0.3-1.0 individuals/m 2 ; Trisel 2003, Christopher et al 2014).…”
Section: Methodssupporting
confidence: 85%
“…This study was conducted at Busch Wildlife Conservation Area (38.708 N, 90.718 W), a 6987-ha reserve in Saint Charles County, Missouri, USA. The area has approximately 1215 ha of oak-hickory forests with shrub layers often dominated by L. maackii , Orrock et al 2012. Density of L. maackii in invaded areas within the study area was 0.34-0.93 individuals/m 2 (Watling et al 2011), densities consistent with other studies (e.g., 0.3-1.0 individuals/m 2 ; Trisel 2003, Christopher et al 2014).…”
Section: Methodssupporting
confidence: 85%
“…; Orrock et al. ; Phillips and Murray ). Because these treatments eliminate large portions of the microbial diversity present in soils, including both pathogens and nonpathogens, the interpretation of the results from such treatments is particularly challenging when attempting to ascribe cause and effect.…”
Section: Introductionmentioning
confidence: 99%
“…Inferences linking plant performance with selective soil microbial enhancement commonly rely solely on comparative plant growth responses in soils conditioned either by the introduced non-native or the native species. In some cases, conditioned soils are either treated with fungicides or sterilized (Reinhart et al 2003(Reinhart et al , 2005Callaway et al 2004;Nijjer et al 2007;MacKay and Kotanen 2008;Petermann et al 2008;Reinhart and Clay 2009;Flory et al 2011;Maron et al 2011;Orrock et al 2012;Phillips and Murray 2012). Because these treatments eliminate large portions of the microbial diversity present in soils, including both pathogens and nonpathogens, the interpretation of the results from such treatments is particularly challenging when attempting to ascribe cause and effect.…”
Section: Introductionmentioning
confidence: 99%
“…Germination may be inhibited by anaerobic conditions that develop during prolonged flooding in bottomland areas (Swab et al 2008) or prolonged (≥12 months) periods of dryness (Hidayati et al 2002). Orrock et al (2012) reported that fungal seed pathogens cause significant seed mortality in L. maackii, but that pathogen attack of honeysuckle seeds was density dependent. This suggests that changes in the soil chemical environment and/or microclimate following L. maackii invasion may be important in mediating fungal effects on seed mortality.…”
Section: Germination and Seedling Establishmentmentioning
confidence: 99%